Frameworks de aplicações orientadas a objetos : uma abordagem interativa e incremental - Carneiro, Cristiane Marise Pérez da Silva (2003)
Software reuse is one of the most important approaches used to improve software quality and to reduce software costs and development time. Object-oriented (OO) programming is often cited as a means to achieve software reuse. Object-oriented frameworks can be used to promote software reuse both at implementation and architectural levels. However, there are several difficulties associated with OO framework development and use. The most notable ones are the framework project complexity and difficulty to reuse. This dissertation presents an iteractive and incremental approach for objectoriented framework development. The approach creates a family of OO frameworks with increasing degree of sophistication, meaning that each framework of the family has more functionality than the previous one. Besides, each framework of the family is by itself a complete and usable framework. This approach reduces the development risk by following a stepwise process to produce, at each development cycle, frameworks that are incrementally more sophisticated than the previous ones. This approach also reduces reuse complexity by offering to the application developer a family of frameworks, which ranges from simple to more complex frameworks. This allows the developer to choose the framework that is best suited to his needs. Lastly, this dissertation presents a case study that enacts our approach by creating a family of three frameworks, and from them developing three applications - one for each of the frameworks.